2012
DOI: 10.1016/j.ejvs.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Subtypes in Symptomatic Carotid Artery and Femoral Artery Plaques

Abstract: Plaques from patients with recently symptomatic carotid disease have a predominance of M1-macrophages and higher lipid content than femoral plaques, consistent with a more unstable plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 24 publications
5
62
1
7
Order By: Relevance
“…Shaikh et al found a higher proportion of M1 proinflammatory macrophages and a reduced proportion of M2 cells in symptomatic carotid lesions (21). The discrepancy to our study could be due to the fact that the former study compared the ratio of macrophage subtypes in the carotid artery with those in vascular femoral plaques.…”
Section: Discussioncontrasting
confidence: 54%
“…Shaikh et al found a higher proportion of M1 proinflammatory macrophages and a reduced proportion of M2 cells in symptomatic carotid lesions (21). The discrepancy to our study could be due to the fact that the former study compared the ratio of macrophage subtypes in the carotid artery with those in vascular femoral plaques.…”
Section: Discussioncontrasting
confidence: 54%
“…The observed macrophage population was relatively more resistant to formation of foam cells and had increased ability to store engulfed cholesterol esters compared to M1 and resting macrophages. M1-specific markers were shown to be increased in carotid atherosclerotic lesions while M2 markers were preferentially located in femoral atherosclerotic plaques [41]. In addition, plaque M1 macrophages were shown to have up-regulated expression of several MMPs [42].…”
Section: Phenotypes Of Macrophages In Atherosclerotic Plaquesmentioning
confidence: 98%
“…M1 macrophages are considered more destructive, promoting the destabilisation and rupture of atherosclerotic plaques, whereas phagocytosis is more important in the role of M2 macrophages stimulating reparative processes, mediated by the production of anti-inflammatory cytokines and the suppression of pro-inflammatory signalling. 39 It has been suggested that 18 F-FDG and USPIO uptake may be able to differentiate these two distinct M1 and M2 macrophage sub-populations respectively. 40 In this study, the majority of 18 F-FDG uptake was identified in the shoulder region of the aneurysm, an area of high biomechanical stress, 41,42 with a particular tendency to rupture: perhaps related to a destructive macrophage phenotype in this area.…”
Section: Discussionmentioning
confidence: 99%